Discovering Our Past: A History of the World - Spielvogel, Jackson J. (United States : McGraw-Hill Education, 2014)
Maximize learning and minimize preparation time with lesson plans, activities, and assessment support based on the research of Jay McTighe, co-author of Understanding by Design
Keywords: Lesson plans; Activities; Assessment Support